ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI HASIL BELAJAR SISWA : STUDI KASUS HASIL PENILAIAN TENGAH SEMESTER MATEMATIKA - Yanti, Aning Wida; Irwanto, Mokhamad Zazuli; Rofikha, Deva Anggia; Kautsar, Amsal; Septiane, Sinta Miftakul Husna; Mas’ullah, siti (Universitas Mercu Buana Yogyakarta, 2023)
Student learning outcomes are a key indicator for measuring educational achievement. The level of academic performance reflects the extent to which students have successfully achieved their educational goals. The purpose of this study is to identify the factors that influence students’ academic achievement. The research was conducted at SMAN 1 Taman Sidoarjo, specifically involving students from class X E 3. The research method used was descriptive qualitative. Qualitative data were obtained from interviews and students' midterm exam (PTS) results. Data collection was carried out in three stages: observation, interviews, and documentation. The findings of this study reveal that the learning outcomes of students at SMAN 1 Taman were not met due to two main factors. These two primary factors influencing academic performance are internal and external factors. The internal factor that affected students’ academic achievement was time management. The external factors included ineffective teaching methods, last-minute distribution of study guides, limited time for completing exams, inconsistency between the study guide and the exam questions, and a new exam application system for grade X students, which caused various difficulties.